Implementasi Kebijakan Program Gerakan Daerah Angkat Anak Muda Putus Sekolah di Dinas Pendidikan Kabupaten Banyuwangi - Putranda, Dicky; Helpiastuti, Selfi Budi; Hara, Abubakar Eby (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
This research is closely related to the problem and is the direction of the answer from the hypothesis or a temporary description of the assumptions. Based on the formulation of the problem that has been stated, the goal to be achieved in this study is to analyze the implementation of the Regional Movement for Lifting Out-of-School Youth Program in Banyuwangi Regency. The Regional Movement Program to Raise School Dropout Youths is part of the Banyuwangi Regency Government's efforts to provide education to the community, especially school children who come from poor communities. The Regional Movement for Lifting Out-of-School Youth is an ideally good program, but it requires accuracy in implementing, utilizing and utilizing it by the community. If this can be done, then the results can have a positive impact on the development of Banyuwangi district in the future. Therefore, on this occasion the researchers conducted research with the title "Policy Implementation of the Regional Movement Program for Lifting Out-of-School Youth at the Banyuwangi District Education Office. The research method used in this research This research uses a qualitative approach (naturalistic research) which places more emphasis on aspects of understanding in depth on a problem. So that this method uses observation, interview, and documentation data collection techniques which will later be tested for validity. The data analysis used is an interactive data analysis method, where this data analysis will later include data collection, data condensation, data presentation, and drawing conclusions.